Comparative tests of concrete building blocks - Bowman, Roy C.; Denneler, Alexander H. (My University, 1907)
Introduction: The object of this thesis is to determine the relative strength of concrete building blocks, (a) When made of different proportions of cement, sand and grit or gravel. (b) When made wet and dry. (c) When made face down and side down. Also to determine the cost of manufacturing the blocks, their fire resisting qualities and the durability of certain mineral colors when mixed in the face of the blocks. Groups M & N, O & P, I & R, S & T, W & V, and W & X, were made in the fall of 1906 by Mr. A. E. Ridenour for the mechanical engineering department. Some of these blocks were broken in curing so we filled out the groups and made such other blocks as were needed to make a complete test.
Citation: Bowman, Roy C. and Denneler, Alexander H. Comparative tests of concrete building blocks. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Concrete; Building Materials; Strength of Materials; Material Properties; Theses